Bibliometric and visualized analysis of hydrogels in organoids research - Jia-bo Wang; Jie Wu; Jian Zhang; Li-an Guan; Hai-bo Feng; Ke-yan Zhu; Yu Zhang; Wen-jie Zhao; Qing Peng; Bo Meng; Sheng Yang; Hua Sun; et al. (Regenerative Therapy, 2024)
Over the past decades, there has been ongoing effort to develop complex biomimetic tissue engineering strategies for in vitro cultivation and maintenance of organoids. The defined hydrogels can create organoid models for various organs by changing their properties and various active molecules. An increasing number of researches has been done on the application of hydrogels in organoids, and a large number of articles have been published on the topic. Although there have been existing reviews describing the application of hydrogels in the field of organoids, there is still a lack of comprehensive studies summarizing and analyzing the overall research trends in this field. The citation can be used as an indicator of the scientific influence of an article in its field. This study aims to evaluate the application of hydrogels in organoids through bibliometric analysis, and to predict the hotspots and developing trends in this field.